2000
DOI: 10.1021/bp0000611
|View full text |Cite
|
Sign up to set email alerts
|

Production of D−Amino Acid Using Whole Cells of Recombinant Escherichiacoli with Separately and Coexpressed D−Hydantoinase and N‐Carbamoylase

Abstract: We developed a fully enzymatic process employing D-hydantoinase and N-carbamoylase for the production of D-amino acid from 5'-monosubstituted hydantoin. For the comparison of the reaction systems using two sequential enzymes, D-hydantoinase of Bacillus stearothermophilus SD1 and N-carbamoyl-D-amino acid amidohydrolase (N-carbamoylase) of Agrobacterium tumefaciens NRRL B11291 were separately expressed in each host cell and coexpressed in the same host cell. A high level and constitutive expression of both enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
28
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 22 publications
3
28
0
Order By: Relevance
“…The homologous enzymes in microorganisms are hydantoinases (HYDs) which catalyze the hydrolysis of 5-substituted hydantoins to the enantiomerically pure Ncarbamyl amino acids. The latter can be converted chemically or enzymatically to the corresponding optically pure amino acids (50,54,64). In the biotechnology industry, HYD is widely used in the production of D-amino acids, including D-p-hydroxyphenylglycine, which are the precursors for semisynthesis of antibiotics, peptide hormones, pyrethroids, and pesticides (3,49,53,54).…”
mentioning
confidence: 99%
“…The homologous enzymes in microorganisms are hydantoinases (HYDs) which catalyze the hydrolysis of 5-substituted hydantoins to the enantiomerically pure Ncarbamyl amino acids. The latter can be converted chemically or enzymatically to the corresponding optically pure amino acids (50,54,64). In the biotechnology industry, HYD is widely used in the production of D-amino acids, including D-p-hydroxyphenylglycine, which are the precursors for semisynthesis of antibiotics, peptide hormones, pyrethroids, and pesticides (3,49,53,54).…”
mentioning
confidence: 99%
“…Previous works have suggested that the D-carbamoylase enzyme step limits the overall process and consequently causes high accumulation of the intermediate (N-carbamoyl-D-amino acid) in the reaction (14,19). For this reason, the D-carbamoylase gene was cloned closest to the promoter in order to obtain the highest synthesis of D-carbamoylase among the three enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…This method is both cheaper and less contaminating than the chemoenzymatic process (10). In this cascade of reactions, named the hydantoin process (1) (4,8,19), only 50% of the remaining hydantoins are converted to the corresponding amino acid, while the other 50% correspond to L-hydantoin, which is not hydrolyzed by D-hydantoinase. For these hydantoins, faster racemization is possible via an enzymatic reaction incorporating a third enzyme named hydantoin racemase together with D-hydantoinase and D-carbamoylase enzymes.…”
mentioning
confidence: 99%
See 2 more Smart Citations